2022
DOI: 10.1186/s13098-022-00944-4
|View full text |Cite
|
Sign up to set email alerts
|

Cooling down with Entresto. Can sacubitril/valsartan combination enhance browning more than coldness?

Abstract: Background It is a growing importance to induce a new treatment approach to encourage weight loss but also to improve maintenance of lost weight. It has been shown that promotion of brown adipose tissue (BAT) function or acquisition of BAT characteristics in white adipose tissue (terms referred as “browning”) can be protective against obesity. Main text Amongst numerous established environmental influences on BAT activity, cold exposure is the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 142 publications
0
0
0
Order By: Relevance
“…However, finding pharmacological manipulation that will favor brown-like adipocytes in WAT depots influencing overall glucose metabolism and energy homeostasis still represents the primarily focus of many investigations. 5 In order to examine the mechanism by which 4-week Sac/Val treatment induces browning in rats with MetS, we investigated the influence of Sac/Val administration on the morphological changes in different adipose tissue depots (sWAT, rWAT, and eWAT). Histological analysis confirmed that MetS induction resulted in increased cell size in each examined adipose tissue related with the accumulation of lipid droplets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, finding pharmacological manipulation that will favor brown-like adipocytes in WAT depots influencing overall glucose metabolism and energy homeostasis still represents the primarily focus of many investigations. 5 In order to examine the mechanism by which 4-week Sac/Val treatment induces browning in rats with MetS, we investigated the influence of Sac/Val administration on the morphological changes in different adipose tissue depots (sWAT, rWAT, and eWAT). Histological analysis confirmed that MetS induction resulted in increased cell size in each examined adipose tissue related with the accumulation of lipid droplets.…”
Section: Discussionmentioning
confidence: 99%
“…Val, as an antagonist of AT1 receptors, partially activates PPARγ which acts as the master regulators of adipogenesis. 5 Recent evidence implied strong correlation between PPARγ stimulation and mTORC1 activation in the management of fat cell metabolism. While PPARγ-mTORC1 activation leads to increased adiponectin production and its secretion in WAT, the downregulation of mTORC1 decreased adipose tissue activity of PPARγ as one of the main regulators of adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations